Motivasi - chikita mayumi midhy; Ni Made Ariani; Agung Sri Sulistyawati (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2021)
online travel agent globally is popular as sources of information search for hotel business choices when planning trips. 65% of leisure tourists and 67% of business travelers search for information via the internet. The internet provides many opportunities to make promotional channels with the presence of OTA websites, hotel websites, and mobile applications. The existence of online sites can motivate domestic and foreign tourists to make online reservations at Padma Resort Legian making it easy to book hotel rooms, get information, and be flexible. The purpose of this study is to determine the factors that encourage tourists to make online reservations at Padma Resort Legian and the dominant factors that motivate tourists to make online reservations at Padma Resort Legian. The technique of determining the number of samples using quota sampling distributed 100 respondents, sampling using judgment sampling techniques. Collection techniques consist of: observation, questionnaire, interview, literature study, and documentation. Qualitative and quantitative descriptive data analysis techniques consisting of: descriptive statistics in the form of Likert scale, statistical inference using factor analysis techniques. Testing the validity test instruments and reliability testing. The results showed there were 5 motivational factors with a total value of variance of 63,426% which encouraged tourists to make online reservations at Padma Resort Legian including: (1) product; (2) superior service; (3) situational & economic; (4) pragmatic; (5) social. The dominant factor in making online reservations at Padma Resort Legian is the product motivation factor with a total value of variance of 34,817%. This factor consists of: getting points, special needs, product availability, product quality, and product variations.